Contribution to the pathogenic fungi on woody plants in North Korea - Pastirčáková, Katarína; Shin, Hyeon-Dong (Phytotaxa, 2017)
This paper presents the first checklist of pathogenic fungi on woody plants in North Korea. The checklist enumerates 146 species of fungi belonging to 79 genera, growing on 108 host plants belonging to 58 genera and 35 families. Two hosts and 57 fungal species represent first records in North Korea.